Lung tumour secretome and extracellular vesicles: mechanisms, biomarkers, and therapeutic opportunities - Kota Shimizu; Yuanzheng Xia; Graeme Stuart Cottrell; Darius Widera (Cancer and Metastasis Reviews, 2026)

Integrating Place Attachment into Management Frameworks: Exploring Place Attachment Across the Recreation Opportunity Spectrum - Christopher J. Wynveen; Ingrid E. Schneider; Arne Arnberger; Stuart Cottrell; Eick von Ruschkowski (Environmental Management, 2020)
The importance of place in landscape management and outdoor recreation has been prominent in the literature since the 1970s. As such, calls to incorporate place into the management of parks, forests, and other protected areas exist. However, little work explores how place attachment may complement existing management frameworks. Hence, the purpose of this investigation was to explore levels of visitors’ place attachment intensity across the six classes of the Recreation Opportunity Spectrum (ROS). Survey data collected in North America and Europe indicated there was more similarity in place attachment intensities among areas classified toward the less developed end of the ROS, while greater variation existed among the more developed sites. Observing place attachment across all six ROS classes allowed for a deeper understanding of the correlation between place and the management framework.

Adaptive capacity in social–ecological systems: a framework for addressing bark beetle disturbances in natural resource management - Stuart Cottrell; Katherine M. Mattor; Jesse L. Morris; Christopher J. Fettig; Pavlina McGrady; Dorothy Maguire; Patrick M. A. James; Jennifer Clear; Zach Wurtzebach; Yu Wei; Andrea Brunelle; Jessica Western; et al. (Sustainability Science, 2020)

Modeling Impacts of Bark Beetle Infestations on Forest Visitor Experiences and Intended Displacement - Ingrid E Schneider; Arne Arnberger; Stuart P Cottrell; Eick von Ruschkowski (Forest Science, 2019)
Bark beetle outbreak impacts are occurring at reportedly unprecedented levels. Despite previous research on the aesthetic and economic impacts of terrestrial pest infestations, minimal visitor behavioral response research exists. As beetle infestation progresses, both tree appearance and landscape change can negatively impact visitation and visitor revenue. Given the multiple-use mandate of most forests, this lack of research is surprising. To meet this gap, this study simulated impacts of varied beetle outbreak levels, management approaches, and visitor characteristics on interference with forest visitors’ experience and intended displacement. Visitors at two forested US state park study sites, one with significant bark beetle impact and the other with much less, responded to onsite questionnaires with digitally calibrated photos depicting a variety of beetle-impacted forest scenarios. Up to 80 percent of visitors indicated forest scenarios with significant bark beetle impact would interfere with their experience, and 70 percent reported they would not visit or be displaced. Analyses revealed forest fore- and midground conditions with varying levels of impact significantly predicted both experience interference and displacement. The relative importance of social, biophysical, and managerial conditions differed between models. Results inform management and planning efforts as well as advance understanding of the biophysical and social factors influencing interference and intended displacement.

Visitor Preferences for Visual Changes in Bark Beetle-Impacted Forest Recreation Settings in the United States and Germany - Arne Arnberger; Martin Ebenberger; Ingrid E. Schneider; Stuart Cottrell; Alexander C. Schlueter; Eick von Ruschkowski; Robert C. Venette; Stephanie A. Snyder; Paul H. Gobster (Environmental Management, 2018)

Population genetics of Formica aquilonia wood ants in Scotland: the effects of long-term forest fragmentation and recent reforestation - Tytti Vanhala; Kevin Watts; Stuart A’Hara; Joan Cottrell (Conservation Genetics, 2014)

Characterisation of thirteen polymorphic microsatellite markers for cowslip (Primula veris L.) developed using a 454 sequencing approach - Charlotte Bickler; Stuart A’Hara; Joan Cottrell; Lucy Rogers; Jon Bridle (Conservation Genetics Resources, 2013)

Development and characterisation of ten polymorphic microsatellite markers for the pine-tree lappet moth Dendrolimus pini (Lepidoptera: Lasiocampidae) - Stuart A’Hara; Joan Cottrell (Conservation Genetics Resources, 2013)

Predicting Stakeholder Support for Fishery Policies - Arren Mendezona Allegretti; Jerry J. Vaske; Stuart Cottrell (Coastal Management, 2012)